2014
DOI: 10.1074/jbc.m114.565028
|View full text |Cite
|
Sign up to set email alerts
|

A Mitogen-activated Protein Kinase/Extracellular Signal-regulated Kinase Kinase (MEK)-dependent Transcriptional Program Controls Activation of the Early Growth Response 1 (EGR1) Gene during Amino Acid Limitation

Abstract: Background: Increased transcription by mammalian amino acid response (AAR) has been linked primarily to the GCN2/ eIF2/ATF4 pathway. Results: Some cells contain a GCN2-and ATF4-independent AAR pathway that is MEK-dependent. Conclusion: A novel MEK pathway activates a specific subset of AA-responsive genes. Significance: The mammalian AAR network is more complex than previously thought, extending beyond the GCN2/eIF2/ ATF4 pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 50 publications
2
34
0
Order By: Relevance
“…We also observed that ATF4/CHOP-independent genes involved in activation of the AAR pathway (33,34) were induced by VGCC/K Ca block ( Fig. 3E; Table 2).…”
Section: Reactome Analysis Identifies Induction Of Aar In Addition Tomentioning
confidence: 54%
“…We also observed that ATF4/CHOP-independent genes involved in activation of the AAR pathway (33,34) were induced by VGCC/K Ca block ( Fig. 3E; Table 2).…”
Section: Reactome Analysis Identifies Induction Of Aar In Addition Tomentioning
confidence: 54%
“…It is a controversial topic on the roles of Egr-1 in HCC. Hao and his colleagues reported that Egr-1 expression was down-regulated in hepatocellular carcinoma, and re-expression of Egr-1 decreased cell growth and tumorigenicity in nude mice [42]. Conversely, Tian et.…”
Section: Discussionmentioning
confidence: 94%
“…8C ) does not perfectly mimic EGR1 induction by serum, but it is similar at the pre-mRNA level. Because EGR1 induction is likely at the level of RNA synthesis [ 64 , 65 , 89 , 90 ], it remains possible that ORF57 is initiating this transcriptional response. If ORF57 induces EGR1, it is not fully induced as there is still an ~10-fold induction of EGR1 mRNA in the presence of ORF57 (compare mRNA levels at 0 with 30 min, Fig.…”
Section: Discussionmentioning
confidence: 99%